Analysis of Rainfall Trends and Its Relationship with SST Signals in the Lake Tana Basin, Ethiopia - Tesfay Mekonnen Weldegerima; Tadesse Terefe Zeleke; Belay Simane Birhanu; Benjamin Frederick Zaitchik; Zewdu Alamineh Fetene (Advances in Meteorology)
The impacts of climate change and climate variability on human life have led the scientific community to monitor the behavior of weather and climate variables at different spatial and temporal scales. This paper explores seasonal and annual trends of rainfall in the Lake Tana basin (LTB) and their teleconnections with global sea surface temperatures (SSTs) over the period between 1979 and 2015. The nonparametric Mann–Kendall test and Sen’s slope estimate are applied to the rainfall data collected from the National Meteorology Agency (NMA) of Ethiopia for detecting and estimating rainfall trends. Additionally, Pearson’s correlation coefficient method is used to determine the effect of SST variations on rainfall. The assessment of rainfall trends indicates that the amount of annual rainfall in the Lake Tana basin is increasing, but the rate of increase is not statistically significant. Seasonal analysis reveals that the smallest amount of rainfall occurs in the Bega season, and this season is getting drier with time. However, the analysis indicates that the other two seasons (Belg and Kiremt) are becoming wetter. The rainfall in Kiremt is increasing significantly (significant at the p=0.05 level) in Debre Tabor station with a rate of 10.20 mm/year. Besides, 78.1% of the total annual rainfall in the basin occurs during this rainy (Kiremt) season, whereas Bega and Belg contribute some 9.4% and 12.5%, respectively. Furthermore, the correlation analysis of rainfall and SSTs indicates that rainfall of the LTB is highly affected by the variations of SSTs.